Patient's point of view on the diagnosis, treatment, and follow-up in acromegaly: single-center study from a tertiary center - Dirikoç,Ahmet (2022)
SUMMARY OBJECTIVE: We aimed to evaluate the awareness and perspectives of acromegaly patients in the diagnosis and treatment processes and to evaluate basic clinical and demographic features. METHODS: This cross-sectional study was conducted at the Endocrinology Department of Yildirim Beyazit University between March 2019 and April 2020. A total of 58 acromegalic patients were enrolled. All patients were identified from our database and called for a clinical visit and filling the questionnaire forms. RESULTS: A total of 58 patients were included in this study (41.4% female). The mean age of the patients was 52±10.8 years. Median year from symptom to diagnosis (min-max) was 2 (1–12). Notably, 55.2% of the patients did not graduate from high school. Of the 58 patients, 30 (51.7%) patients had knowledge about the etiology of their disease. While 12 (20.7%) patients identified their initial symptoms themselves, 75% of the patients reported their symptoms during the clinical history taken by a health care professional. The majority of patients were diagnosed by an endocrinologist (69%). Acromegaly did not affect social life but affected work life and caused early retirement. Transsphenoidal surgery was performed as primary treatment in 96.6% of the patients (n=56). In all, 46 (79.3%) patients received medical treatment with somatostatin receptor ligands (e.g., octreotide or lanreotide long-acting release [LAR]) with or without cabergoline. Overall disease control was achieved in 38 (65.5%) patients. CONCLUSIONS: Acromegaly is usually detected incidentally by clinicians. The diagnosis of acromegaly is delayed in most patients and disease-related complications have already developed at the time of diagnosis. Therefore, increasing the awareness of the society and health care professionals will reduce both disease-related comorbidities and the economic burden on the health system.